Effect of rejection sensitivity on the development of anxious-depressive attack in Japanese outpatients: The mediating roles of rumination, social anxiety, and depressive symptoms - Noda, Shota; Masaki, Mina; Kishimoto, Tomokazu; Kaiya, Hisanobu (Frontiers in Psychology, 2022)
Objective: Anxious-depressive attack (ADA) is a cluster of symptoms, including sudden and intense anxiety or depression, intrusive rumination about negative memories or future worries, prominent agitation, impatient behavior, and/or loneliness; in some cases, symptoms include a wide range of violent coping behaviors to manage emotional distress. Four characteristics—rejection sensitivity, ruminative thinking, social anxiety symptoms, and depressive symptoms—are thought to be associated with the development of ADA. However, the complex relationships among these factors have not been clarified. In this study, we aimed to examine the mechanism by which these four characteristics influence the development of ADA. Method: We conducted a structured interview about ADA with 332 outpatients, who completed several self-report measures, to assess rejection sensitivity, ruminative thinking, social anxiety symptoms, and depressive symptoms. Results: A structural equation model showed goodness-of-fit with the data. These findings suggest that rejection sensitivity may demonstrate a direct effect on the occurrence of ADA. Furthermore, rejection sensitivity might affect depressive symptoms through ruminative thinking and social anxiety and consequently contribute to the development of ADA. Conclusions: These results provide preliminary evidence that rejection sensitivity contributes to the development of ADA.